Saponin components in Polygala tenuifolia as potential candidate drugs for treating dementia - Li, Songzhe; Hou, Zhitao; Ye, Ting; Song, Xiaochen; Hu, Xinying; Chen, Jing (Frontiers in Pharmacology, 2024)
Objective This study aims to elucidate the intervention effects of saponin components from Polygala tenuifolia Willd (Polygalaceae) on dementia, providing experimental evidence and new insights for the research and application of saponins in the field of dementia. Materials and Methods This review is based on a search of the PubMed, NCBI, and Google Scholar databases from their inception to 13 May 2024, using terms such as “P. tenuifolia,” “P. tenuifolia and saponins,” “toxicity,” “dementia,” “Alzheimer’s disease,” “Parkinson’s disease dementia,” and “vascular dementia.” The article summarizes the saponin components of P. tenuifolia, including tenuigenin, tenuifolin, polygalasaponins XXXII, and onjisaponin B, as well as the pathophysiological mechanisms of dementia. Importantly, it highlights the potential mechanisms by which the active components of P. tenuifolia prevent and treat diseases and relevant clinical studies. Results The saponin components of P. tenuifolia can reduce β-amyloid accumulation, exhibit antioxidant effects, regulate neurotransmitters, improve synaptic function, possess anti-inflammatory properties, inhibit neuronal apoptosis, and modulate autophagy. Therefore, P. tenuifolia may play a role in the prevention and treatment of dementia. Conclusion The saponin components of P. tenuifolia have shown certain therapeutic effects on dementia. They can prevent and treat dementia through various mechanisms.